Age- and gender-related radiological changes of the cervical spine: A study with largest magnetic resonance imaging database of 5672 consecutive patients - Ali Riza Guvercin; Erhan Arslan; Cigdem Hacifazlioglu; Ayhan Kanat; Elif Acar Arslan; Ugur Yazar (Journal of Craniovertebral Junction and Spine, 2023)
Background: The morphological features of the cervical spine are an essential issue. This retrospective study aimed to investigate the structural and radiological changes in the cervical spine. Materials and Methods: A total of 250 patients with neck pain but no apparent cervical pathology were selected from a database of 5672 consecutive patients undergoing magnetic resonance imaging (MRI). MRIs were directly examined for cervical disc degeneration. These include Pfirrmann grade (Pg/C), cervical lordosis angle (A/CL), Atlantodental distance (ADD), the thickness of transverse ligament (T/TL), and position of cerebellar tonsils (P/CT). The measurements were taken at the positions of T1- and T2-weighted sagittal and axial MRIs. To evaluate the results, patients were divided into seven age groups (10–19, 20–29, 30–39, 40–49, 50–59, 60–69, 70, and over). Results: In terms of ADD (mm), T/TL (mm), and P/CT (mm), there was no significant difference among age groups (P > 0.05). However, in terms of A/CL (degree) values, a statistically significant difference was observed among age groups (P < 0.05). Conclusions: Intervertebral disc degeneration was more severe in males than in females as age increased. For both genders, cervical lordosis, decreased significantly as age increased. T/TL, ADD, and P/CT did not significantly differ with age. The present study indicates that structural and radiological changes are possible reasons for cervical pain at advanced ages.